2017
DOI: 10.4012/dmj.2016-279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ice-quenching on the change in hardness of a Pd-Au-Zn alloy during porcelain firing simulation

Abstract: This study examined the effect of ice-quenching after degassing on the change in hardness of a Pd-Au-Zn alloy during porcelain firing simulations. By ice-quenching after degassing, the specimens were softened due to homogenization without the need for an additional softening heat treatment. The lowered hardness by ice-quenching after degassing was recovered greatly from the first stage of porcelain firing process by controlling the cooling rate. The increase in hardness during cooling after porcelain firing wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…From the above, it can be determined that oxidation followed by ice-quenching reduced the hardness temporarily without sacrificing the final hardness at both, the relatively high and low cooling rates (p < 0.05). In previous studies that used a single cooling rate, such a recovery of hardness was observed in Pd−Au and Pd−Cu alloys, as well as in Pd-Ag alloy [8,9,13]. In particular, in Pd−Cu alloys, the final hardness far exceeded that of the non-quenched alloy [13].…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…From the above, it can be determined that oxidation followed by ice-quenching reduced the hardness temporarily without sacrificing the final hardness at both, the relatively high and low cooling rates (p < 0.05). In previous studies that used a single cooling rate, such a recovery of hardness was observed in Pd−Au and Pd−Cu alloys, as well as in Pd-Ag alloy [8,9,13]. In particular, in Pd−Cu alloys, the final hardness far exceeded that of the non-quenched alloy [13].…”
Section: Discussionmentioning
confidence: 72%
“…Thus, if the alloy is rapidly quenched in ice brine (ice-quenching, IQ) Metals 2021, 11, 680 2 of 13 in place of the normal cooling step after oxidation, the hardness can be lowered without performing an additional heat treatment. In previous studies, the hardness of Pd-based alloys was lowered by oxidation treatment followed by ice-quenching, and recovered thereafter as firing proceeded [8,9]. Therefore, ice-quenching after oxidation was thought to be effective in softening the alloy to enable easy trimming without sacrificing the final hardness.…”
Section: Introductionmentioning
confidence: 99%